INTERFACE ENTRE A REDE DE ATENÇÃO À SAÚDE E AS DEMANDAS DE URGÊNCIA EM SAÚDE BUCAL EM PRONTO ATENDIMENTO MUNICIPAL - Mai, Larissa Menezes (2024)
The general aim of the study was to analyze the urgent demands for oral health in a municipal emergency service (PAM), relating them to the organization of the health care network in a city in the central region of Rio Grande do Sul, Brasil. The specific objectives were defined: to characterize user care at PAM due to oral health emergencies; and to understand the conceptions of professionals from the oral health team regarding attention to urgent demands in the daily routine of dental care at PAM. Methods: This is an exploratory, descriptive study, with a quantitative and qualitative approach. The study was developed in the Dentistry Service of a PAM in the central region of Rio Grande do Sul. The quantitative step, of a documentary nature, included data collection in the MV/Consulfarma System, searching for information in medical records of patients treated at the PAM during the months of October, November and December 2023, totaling 1220 consultations in the period. The variables used were gender, age, place of residence and reason for care. The collected data was organized in Excel spreadsheets, presented through graphs and analyzed using simple descriptive statistics. The qualitative step was developed through semi-structured interviews. Six professionals working in the PAM dentistry service participated in the study, including four dental surgeons and two oral health assistants. After carrying out the interviews, the data was organized and analyzed according to thematic content analysis. Data collection was carried out from November 2023 to February 2024. The study was approved by the Research Ethics Committee, being registered under number 5.918.151. Results: Females searched the emergency service more often, resulting in 618 (50.7%) visits in total, while males totaled 602 (49.3%). According to age group, the majority of visits were from young adults, between 23 and 29 years of age, totaling 196 (16.05%) procedures. It is noteworthy that 687, that is, 56.29% of the services were centered on the age group from 23 to 52 years old, which characterizes a portion of the population of productive age for the job market and, therefore, who would be unlikely to be able to access the Primary Health Care (PHC) during its opening hours. Regarding the reason for the consultation, most of the consultations were related to pulpitis cases, which made up a total of 517 (42.38%). With regard to place of residence, the West region was the one that centralized 564 (46.23%). In relation to the data from the interviews, it was possible to organize them into two main thematic categories: Understanding the motivations for seeking emergency dental services; and Identifying (dis)connections in the health care network. These categories demonstrated that, in addition to urgent cases, users seek the service due to insufficient professionals, low PHC coverage and, also, by their own choice, related to flexible schedules and guaranteed service. Conclusion: The study demonstrated that the demands for emergency dental care translate into gaps in the coordination between care networks in the city, both through statements in interviews and through data obtained from medical records. The high demand of patients in the emergency service demonstrated that PHC is weak in prevention and dental health promotion services. It is therefore necessary to implement strategies that integrate the care network, in addition to health policies that guarantee the sufficiency of professionals and the strengthening of services with a view to comprehensive care.